Empowering competency-based talent management in Malaysia’s public universities- A strategic partnership between AKEPT and UMP - Siti Sakinah, Mohtar (2019)
Higher Education Leadership Academy (AKEPT) organised a series of programme on Competency-Based Talent Management (CBTM) called Talent Management for Excellence Series or TaME in 2018.